KORELASI MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS VIII DI SMP NEGERI SE-KECAMATAN JAMBI SELATAN - Saputra, Wisnu Rahmad; Hendri, Menza; Aminoto, Tugiyo (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2019)
The purpose of this research was to know the correlation between motivation with the science learning outcomes of grade VIII students in SMP Negeri in South Jambi district. This research used quantitative approaches with correlational type. Independent variables were learning motivation and dependent variables were the science learning outcomes. Data collection instruments using motivational questionnaire and test of science learning outcomes of work and energy content. Data analysis techniques consist of test normality, and correlation test with a significance level of 5% with the SPSS programe. The result of the correlation of motivation learning with the learning outcomes is 0.356 with SIG 0.00 < 0.05 then H0 rejected. There is a significant correlation between the motivation with the science learning outcomes in class VIII students in SMP Negeri in South Jambi district.